Development of Communication and Language Skills in Children with Hematological–Oncological Disorders: Challenges and Perspectives - Giusy Melcarne; Giulia Marangon; Roberta Maria Incardona; Anna Agostinelli; Silvia Montino; Silvia Sorbara; Alessandra Biffi; Marta Tremolada (Children)
Children with onco-hematological diseases require intensive medical treatments that can affect various aspects of their development. In addition to the disease itself, what influences the course of development most are the neurotoxic effects of therapies and frequent hospitalizations, especially if they occur in the first three years of the child’s life. Among these challenges there is the potential for language delay, a condition that can impact their communication abilities and overall development. Background/Objectives: The aim of this study is to examine communicative and linguistic development in a small group of young children diagnosed with different forms of leukemia, rhabdomyosarcoma, and CNS tumors, recruited through the Hematology–Oncology Clinic of the Department of Child and Woman Health (University of Padova). Methods: Child direct (Griffiths III, PinG, PCGO) and parent indirect assessments (PVB, ABAS-II, ASCB) were provided. Results: Griffiths communication subscale scores in children were mainly below average (55.6%), and 44.4% attested at the clinical level in ABAS-II, with the ability to understand being significantly higher than the production of words. However, the two levels of assertiveness–responsiveness obtained balance in 66.7% of cases, and using the Griffiths personal subscale, only 22.2% of children attested below average. Conclusions: Understanding and addressing children’s communication needs is crucial to improve the quality of life of these young patients and foster optimal communicative and linguistic development despite the obstacles they face in order to implement interventions designed specifically for this type of population and their respective families, if necessary.